1968
DOI: 10.1111/j.1399-3054.1968.tb07256.x
|View full text |Cite
|
Sign up to set email alerts
|

Der Einfluss der Phosphatversorgung sowie die Wirkung von ionogenem und chelatisiertem Zink auf die Zink‐ und Phosphataufnahme einiger Schwermetallpflanzen

Abstract: Zusammenfassung In physiologischen Untersuchungen an Schwermetallpflanzen wurde die hohe Zinkverträglichkeit für Silene cucubalus var. humilis bestätigt und für Thlaspi alpestre ssp. calaminare neu festgestellt. In Wasserkulturversuchen mit Silene cucubalus var. humilis wirkte Zinksulfat bereits bei einer Gabe von 100 mg Zn/1 im Verlauf einer Vegetationsperiode toxisch. Hingegen wurde Zink‐Chelat noch bei einer Konzentration von 600 mg Zn/I ertragen. Durch Chelatgaben kann demnach die Zinkverträglichkeit der S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
1

Year Published

1971
1971
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…calaminare used by Ernst (1968Ernst ( , 1974 came from a high zinc site, it is uncertain whether phosphate ever plays a special role in antagonizing zinc toxicity for plants normally growing in a low zinc environment. It is however well established that high levels of phosphate may induce zinc deficiency in various crops (Burleson & Page, 1967).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…calaminare used by Ernst (1968Ernst ( , 1974 came from a high zinc site, it is uncertain whether phosphate ever plays a special role in antagonizing zinc toxicity for plants normally growing in a low zinc environment. It is however well established that high levels of phosphate may induce zinc deficiency in various crops (Burleson & Page, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…) Markgr. that increased phosphate levels lead to a reduction in zinc toxicity and also to a marked difference in the distribution of zinc inside the plant (Ernst, 1968(Ernst, , 1974. There have apparently been no experimental studies of the factors reducing zinc toxicity to algae, but Keulder (1975) has shown that hydrogen, magnesium, copper and phosphate ions all antagonize the uptake of 65Zn by Scenedesmus obliquus (Turp.…”
mentioning
confidence: 99%
“…For example, Thlaspi caerulescens is a Zn-hyperaccumulator plant discovered in 1865 on a mineral mountain in Europe (Ernst, 1989). Ernst (1968) has reported that T. caerulescens grown in nutrient solution containing 206 mg/L Zn did not show any toxicity symptoms, suggesting that the plant can resist Zn stress. The mechanism of tolerance possibly depends on factors such as restriction of Zn translocation to the shoots, protection of sensitive structures in the cytoplasm by immobilization of metal in the cell wall, or compartmentalization of metal in the vacuole and metal complexion with soluble compounds, e.g.…”
Section: Introductionmentioning
confidence: 97%
“…normally severely toxic concentrations in their shoots (Ernst 1968;Baker & Brooks 1989;Reeves 1992). Most of these species are more or less restricted to strongly metalenriched soil types but some of them are also commonly found on non-metalliferous soil (Ingrouille & Smirnoff 1986;Baker & Proctor 1990;Schat, Llugany & Bernhard 1999).…”
mentioning
confidence: 99%